STUDY ON IMPLEMENTATION OF SOLAR POWER PLANT IN UTP - Fadzil, Muhammad Faris (IRC, 2019)
Universiti Teknologi PETRONAS (UTP) has its own gas turbine power plant that use natural gas to generate electricity for the university uses. The gas turbine is located at gas district cooling of GDC. This power plant receives the natural gas through the underground pipeline that connected from natural gas storage at Lumut to UTP. The power plant can generate up to 8MW of power per day to meet the electricity demand in UTP. Nowadays, the global market for the fossil fuel has been unstable due to the global conflict and global politics. The unstable market price for the crude oil has make be price of the natural gas that are used by GDC to generate electricity has become more expensive over time. This causing some financial issue to the UTP management as the price of to buy the natural gas per month almost the same as price of electric bill when using electricity supplied by TNB. To overcome the problem, UTP plan to stop using the power plant and taking power from national grid (TNB). This study on the implementation of solar power plant in UTP as there are no studies has been carried out on the solar power plant in UTP. The study comprises of study in tern of technical and economic analysis. In term of technical, the study will cover the size of PV system, cost and area needed for the installation of the solar power plant. The study will be done using Homer Pro software to simulate the situation to obtain the necessary data that can be used as guideline for the solar panel implementation. The data will cover the economical aspect and the technical aspect for the study. The economic aspect of this study is to determine the initial cost of installation and return of investment (ROI) of the implementation of solar panel power plant. This is to ensure that the solar power plant carries more economical benefits than current power plant in UTP.